ROLE AND CONTRIBUTION OF PRINTMAKING TO THE MODERN INDIAN ART - Goel, Ashima; Singh, Udaya Narayana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of this research paper is to provide a chance to travel through the process of looking for and discovering new events that occurred throughout the development of printing in India. The constant drive to build and establish printing workshops is where the innovation, handiwork, and creativity that are driving the industry's expansion can be found. Printmaking is an art form that emerges as a result of the combination of technical expertise and creative visualization. One must not only have access to high-quality tools but also be familiar with how to properly use them. Therefore, it is of the utmost importance to have a solid understanding of the various printing processes. The fact that printing was accessible to the general public was the defining characteristic of this century. Because of its accessibility, low cost, ease of communication, and mobility, it quickly rose to prominence among the general population. After a few decades, the same thing that happened in Europe occurred in India as well. In the beginning, the weight that was placed on its practical advantages was mostly because it was thought of as being more technique- or craft-oriented than other modes of expression. In the process of producing works of popular art, the role of the printer was analogous to that of a technician. His approach to language and way of communication never really materialized into something noteworthy. The identities of several of these skilled printmakers were never revealed. In the Western world, many artists turned to print as a means of promoting their work or just experimenting with new mediums. It's interesting to note that the situation was the same in our nation. The sole purpose for which Ravi Varma installed his printing press was to make copies. A great number of Indian artists only utilized printing to experiment, and they were content with producing only a few pieces in this medium. The process of printmaking went through a lengthy development phase until it finally reached the stage of maturity that enabled it to take its rightful place in the center of the printing scene on a global scale